2010
DOI: 10.3233/ch-2010-1282
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide, substance P, nitric oxide and epinephrine modulate bone marrow micro circulation of the rabbit tibia and femur

Abstract: Different bones have different blood supplies, which may influence bone healing. Therefore, elucidation of the mechanisms involved in the regulation of bone marrow blood flow in different bones is of high clinical importance. To assess the micro circulation of bone marrow of the femur and tibia simultaneously, flow velocities were continuously measured by a two-channel laser-Doppler flowmeter. The probes were introduced into the femoral and tibial diaphysis, respectively, in the anesthetized rabbit. Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Specifically, it was found that there was desensitization of arteries upon continued exposure to SP [64]. Vendégh et al [99], however, found no significant effect to bone marrow microvascular resistance from CGRP or SP. Interestingly, increased angiogenesis in calvarial defect sites was noted with use of SP/dexamethasone-encapsulated PLGA scaffolds [100].…”
Section: Substance Pmentioning
confidence: 98%
“…Specifically, it was found that there was desensitization of arteries upon continued exposure to SP [64]. Vendégh et al [99], however, found no significant effect to bone marrow microvascular resistance from CGRP or SP. Interestingly, increased angiogenesis in calvarial defect sites was noted with use of SP/dexamethasone-encapsulated PLGA scaffolds [100].…”
Section: Substance Pmentioning
confidence: 98%
“…ET-1 is a potent vasoconstrictor that activates ET-A receptors in vascular smooth muscle 48 . Other vasodilating substances, secreted by a variety of cells types, such as calcitonin gene related peptide, adrenomedullin and substance P act primarily through increases in NO release from endothelial cells 49,50 . The glucose-regulating gut hormone glucagon-like peptide-1 (GLP-1) also has vasodilating properties 51 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Glucocorticoids have been shown to down‐regulate the expression of endothelial NO synthase in rats 24. It could be shown in the rabbit that NO reduced microvascular resistance 25. Bone vasculature is also believed to play an important role in bone remodeling.…”
Section: Discussionmentioning
confidence: 99%